The interactive alphabet with augmented reality as a form of involving children in educational process - Vladimir D. Sekerin; Anna E. Gorokhova; Anatoliy A. Scherbakov; Evgeniy V. Yurkevich (Открытое образование (Москва))
Research objective: to prove the expediency of using technologies with augmented reality in educational process of children in order to increase the level of their involvement and to improve the efficiency of educational process. Materials and methods. The information base of the research was made by scientific publications, information and analytical reviews, periodicals, monographs, information placed in the Internet network, concerning practical application of technologies with augmented reality in educational process, descriptive and comparative methods of analysis form the methodical basis of this research. Results. It is shown that in educational process of children it is expedient to use the modern technological achievements allowing organizing productive interactions and relationship of the students among themselves and with teachers, lecturers. Educational, business, role-playing games, discussions promoting acceleration of acquiring  a new experience and receiving new knowledge are the perspective formats of realizing the educational process. The world of augmented reality has the following properties: combines the real and virtual, interacts in real time mode, and functions in three-dimensional space. The advantages of the Interactive alphabet on the basis of the augmented reality technology are as follows: 1) security of strong emotional responses; 2) the involvement and interactivity promoting steady memorizing; 3) possibilities of interaction with the artificial world by means of gadgets; 4) Digital and offline communication; 5) possibility of carrying out virtual lessons. One of the main features of virtual reality is the feeling of participation and the opportunity to observe everything from the first person. It makes expedient to carry out lessons entirely in the virtual reality. Achievement of full involvement in educational process promotes increase of motivation and progress in knowledge acquisition.  The use of the augmented reality technologies in educational processes gives a range of unlimited opportunities, to which belong, e.g. participation in historical events; observation of the most unusual physical phenomena; carrying out manipulations with various objects of the physical world; performing chemical experiments; analysis of large volumes of data. Conclusion. Application of the augmented reality technology promotes higher efficiency of educational processes. Use of the virtual reality allows not only telling and showing the world history to pupils, but also illustrating the world of the past from the perspectives of specific historical characters. Pupils can be sent to travel in a human body as in microcapsules and to choose the right course for expeditions by Magellan’s ship. Use of the virtual reality allows changing scenarios, influencing various experiments or solving mathematical problems in forms of understandable games.